The Effect of Baby Massage on Baby Weight Gain - Rochmawati Rochmawati; Sri Hayuningsih; Hellena Yollanita (EMBRIO: Jurnal Kebidanan, 2023)
The most essential anthropometric measurement, body weight is consistently employed to assess the well-being of infants across all age categories. An infant that is in good health exhibits growth in both height and weight. Baby massage is highly beneficial for optimizing the growth and development of children, including increasing food assimilation to hasten the onset of hunger and encouraging more frequent breastfeeding to promote weight gain in infants. Used as an analytic One Group Pre-test – Post-test Design approach. This study was located at TPMB (Independent Midwife Practice Place) Dian Dwi, Bogor Regency, which was carried out in October - December 2022. Sampling was carried out by total sampling, namely all samples available at the time of the study, namely 23 babies. According to the results of the statistical test, the increase in the infant's weight prior to and following the massage differed significantly. Based on the results of interval estimation, it can be deduced that 95 percent of respondents consider the average body weight following a baby massage to be between 5.35 and 5.09. The findings yielded a p-value of 0.000 (count less than a), which indicates that newborn massage has a significant impact on the weight of infants aged 1-12 months at a = 5 percent. The impact of newborn massage on infant weight gain is substantial.